2010
DOI: 10.1007/s00428-010-1023-4
|View full text |Cite
|
Sign up to set email alerts
|

The many faces of atypical Ewing’s sarcoma. A true entity mimicking sarcomas, carcinomas and lymphomas

Abstract: Ewing's sarcoma family of tumours (ESFT) comprises a group of small round cell tumours (SRCT) genetically defined by specific chromosomal translocations resulting in a fusion of the EWSR1 gene with a member of the ETS family of transcription factors. Atypical ESFT are the most challenging of the ESFT subtypes, and the differential diagnosis with other SRCT of bone and soft tissue is difficult since these subtypes can resemble other neoplasms. The present article describes nine cases of genetically confirmed, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
37
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 32 publications
0
37
0
Order By: Relevance
“…ESFT appears to have the potential for differentiating toward mesenchymal, neural, and epithelial lineages. The immunohistochemical (IHC) study in a large series of ESFT previously described by Llombart-Bosch et al [2] confirmed the diagnostic value of CD99, HNK1, Fli1, and CAV1, which together cover more than 99% of ESFT and substantiated the mesenchymal and neural differentiation of this neoplasm [2][3][4].…”
Section: Introductionmentioning
confidence: 64%
See 3 more Smart Citations
“…ESFT appears to have the potential for differentiating toward mesenchymal, neural, and epithelial lineages. The immunohistochemical (IHC) study in a large series of ESFT previously described by Llombart-Bosch et al [2] confirmed the diagnostic value of CD99, HNK1, Fli1, and CAV1, which together cover more than 99% of ESFT and substantiated the mesenchymal and neural differentiation of this neoplasm [2][3][4].…”
Section: Introductionmentioning
confidence: 64%
“…Other gene fusions have been described in ESFT, including FUS/ERG, FUS/FEV, EWSR1/PATZ1, EWSR1/SP3, EWSR1/NFATc2, BRD4/NUT, CIC/DUX4 [5,6], and EWSR1/SMARCA5 [7]. The histopathology includes three larger categories according to their predominant morphological criteria: conventional Ewing's sarcoma (ES), peripheral neuroectodermal tumors (PNET), and atypical ES comprising all subtypes distinct from the other two types [2,3]. ESFT appears to have the potential for differentiating toward mesenchymal, neural, and epithelial lineages.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The term ESFT includes typical Ewing's Sarcoma, the Peripheral Neuro ectodermal tumour (PNET) or Askin'stumor of the chest wall [1]. It is the second most malignant tumour in the 10-20 year age group [2].…”
Section: Introductionmentioning
confidence: 99%